Análisis de los precios del café ecuatoriano en el mercado alemán. - Herrera Herrera, Diana Fabiola (My University, 2019)
Ecuador is decreasing its liquidity every day given the outflow of foreign currency by allowing debauchery of imports of all kinds of products. And an irresponsibility of this nature, puts at high risk the sustainability of dollarization, only acting sensibly in foreign trade, that is, allowing imports of items of goods that are destined to the agro-export and industrial development; as well as expand the export of non-traditional products, will allow an encouraging respite to the economy, therefore to the maintenance of dollarization. With the purpose of positively contributing to minimize the problem addressed, it is proposed to increase the level of coffee exports produced in our province to the German market. This market is located in one of the European countries with the highest demand for coffee; it is an importer with a lot of experience in the marketing and consumption of coffee. Through exploratory research it was possible to obtain information that allowed the analysis of prices whose purpose is to know the profit margin generated by the export of coffee to the German market. This integrative project has been developed with knowledge acquired throughout the university career with the diversity of specialized subjects treated during the duration of the same, mentioning among others the following: marketing, financial mathematics, accounting, international law, projects of foreign trade, foreign trade, customs techniques, foreign trade management.
El Ecuador está cada día disminuyendo su liquidez dada la salida de divisas al permitirse libertinaje de importaciones de toda clase de productos. Y una irresponsabilidad de esa naturaleza, pone en altísimo riesgo el sostenimiento de la dolarización, solamente actuando con sensatez en el comercio exterior, es decir, permitiendo importación de rubros de bienes que se destinen al desarrollo agroexportador e industrial; así como, ampliar la exportación de productos no tradicionales, permitirán un respiro alentador a la economía, por ende al mantenimiento de la dolarización. Con el propósito de aportar positivamente a minimizar la problemática abordada, se plantea, incrementar el nivel de exportaciones de café que se produce en nuestra provincia hacia el mercado de Alemania. Este mercado se localiza en uno de los países europeos que presenta mayor demanda de café, es un importador con mucha experiencia en la comercialización y consumo de café. Mediante una investigación se logró obtener información que permitió el análisis de precios cuya finalidad es conocer el margen de utilidad que genera la exportación de café hacia el mercado alemán. Este proyecto integrador se ha desarrollado con conocimientos adquiridos a lo largo de la carrera universitaria con la diversidad de asignaturas de especialización tratadas durante la duración de la misma, mencionando entre otras a las siguientes: marketing, matemáticas financieras, contabilidad, derecho internacional, proyectos de comercio exterior, comercio exterior, técnicas aduaneras, gerencia de comercio exterior.
Keywords: EXPORTACIÓN; COMERCIO INTERNACIONAL; PRODUCCIÓN; OFERTA Y DEMANDA